Improvements to Healthspan Through Environmental Enrichment and Lifestyle Interventions: Where Are We Now? - Queen, Nicholas J.; Hassan, Quais N.; Cao, Lei (Frontiers in Neuroscience, 2020)
Environmental enrichment (EE) is an experimental paradigm that is used to explore how a complex, stimulating environment can impact overall health. In laboratory animal experiments, EE housing conditions typically include larger-than-standard cages, abundant bedding, running wheels, mazes, toys, and shelters which are rearranged regularly to further increase stimulation. EE has been shown to improve multiple aspects of health, including but not limited to metabolism, learning and cognition, anxiety and depression, and immunocompetence. Recent advances in lifespan have led some researchers to consider aging as a risk factor for disease. As such, there is a pressing need to understand the processes by which healthspan can be increased. The natural and predictable changes during aging can also be reversed or decreased through EE and its underlying mechanisms. Here, we review the use of EE in laboratory animals to understand mechanisms involved in aging, and comment on relative areas of strength and weakness in the current literature. We additionally address current efforts towards applying EE to human health to extend healthspan. Although increasing lifespan is a clear goal of medical research, improving the quality of this added time also deserves significant attention. Despite hurdles in translating experimental results towards clinical application, we argue there is great potential in using features of EE towards improving human healthy life expectancy or healthspan, especially in the context of increased global longevity.